The role of TGF-β in the association between primary graft dysfunction and bronchiolitis obliterans syndrome - DerHovanessian, Ariss (Am J Transplant, 2015)
Primary graft dysfunction (PGD) is a possible risk factor for bronchiolitis obliterans syndrome (BOS) following lung transplantation; however, the mechanism for any such association is poorly understood. Based on TGF-β's association with acute and chronic inflammatory disorders, we hypothesized that it may play a role in the continuum between PGD and BOS. Thus, the association between PGD and BOS was assessed in a single-center cohort of lung transplant recipients. Bronchoalveolar lavage fluid concentrations of TGF-β and procollagen collected within 24 hours of transplantation were compared across the spectrum of PGD, and incorporated into Cox models of BOS. Immunohistochemistry localized expression of TGF-β and its receptor in early lung biopsies post-transplant. We found an association between PGD and BOS in both bilateral and single lung recipients with a hazard ratio of 3.07 (95% CI 1.76-5.38) for the most severe form of PGD. TGF-β and procollagen concentrations were elevated during PGD (p<0.01), and associated with increased rates of BOS. Expression of TGF-β and its receptor localized to allograft infiltrating mononuclear and stromal cells, and the airway epithelium. These findings validate the association between PGD and the subsequent development of BOS, and suggest that this association may be mediated by receptor/TGF-β biology.